Antlers [videorecording (DVD)] - Cooper, Scott, 1970-; Chaisson, Henry, 1992-; Antosca, Nick; Russell, Keri, 1976-; Plemons, Jesse, 1988-; Thomas, Jeremy T.; Greene, Graham, 1952-; Haze, Scott; Cochrane, Rory; Madigan, Amy; Hoffmeister, Florian, 1970-; Navarrete, Javier, 1956-; et al. (Searchlight Pictures, 2022)
In a remote Oregon town, a middle-school teacher and her sheriff brother become entangled with her enigmatic student, whose dark secrets lead to horrifying encounters with a legendary ancestral creature who came before them.